EUD for enterprise process and information management - Stoitsev, Todor; Spahn, Michael; Scheidl, Stefan (International Conference on Software Engineering 2008, 2008)
This position paper presents research on End-User Development (EUD) for enterprise systems, which is aiming at improving the ability of Small and Medium Enterprises (SMEs) to adapt their software systems to individual and changing needs. These research efforts can be divided into two main directions: process-centric EUD and data-centric EUD. In particular, two basic sub-domains are addressed: (i) end-user driven business process composition and management as well as (ii) end-user driven composition of data-centric and analytic applications. Both topics are closely related since analytic applications may provide decision support in processes and processes may be the subject of analysis, e.g. for process optimization purposes. Advances in these research topics are presented through a brief overview of the developed concepts.